Swiss Feline Cancer Registry 1965–2008: the Influence of Sex, Breed and Age on Tumour Types and Tumour Locations. Issue 2 (February 2016) - Graf, R.; Grüntzig, K.; Boo, G.; Hässig, M.; Axhausen, K.W.; Fabrikant, S.; Welle, M.; Meier, D.; Guscetti, F.; Folkers, G.; Otto, V.; Pospischil, A.
Summary: Cancer registries are valuable sources for epidemiological research investigating risk factors underlying different types of cancer incidence. The present study is based on the Swiss Feline Cancer Registry that comprises 51, 322 feline patient records, compiled between 1965 and 2008. In these records, 18, 375 tumours were reported. The study analyses the influence of sex, neutering status, breed, time and age on the development of the most common tumour types and on their locations, using a multiple logistic regression model. The largest differences between breeds were found in the development of fibrosarcomas and squamous cell carcinomas, as well as in the development of tumours in the skin/subcutis and mammary gland. Differences, although often small, in sex and neutering status were observed in most analyses. Tumours were more frequent in middle-aged and older cats. The sample size allowed detailed analyses of the influence of sex, neutering status, breed and age. Results of the study are mainly consistent with previous analyses; however, some results cannot be compared with the existing literature. Further investigations are necessary, since feline tumours have not been investigated in depth to date. More accurate comparisons would require the definition of international standards for animal cancer registries.